Selective Auditory Attention Associated With Language Skills but Not With Executive Functions in Swedish Preschoolers - Tonér, Signe; Kallioinen, Petter; Lacerda, Francisco (Frontiers in Psychology, 2021)
Associations between language and executive functions (EFs) are well-established but previous work has often focused more on EFs than on language. To further clarify the language-EF relationship, we assessed several aspects of language and EFs in 431 Swedish children aged 4-6, including selective auditory attention, which was measured in an event-related potential paradigm. We also investigated potential associations to age, socioeconomic status (SES), bi-/multilingualism, sex and aspects of preschool attendance and quality. Language and EFs correlated weakly to moderately, indicating that relying on measures of vocabulary alone may overestimate the strength of the language-EFs relationship. Contrary to predictions, we found no correlations between selective attention and EFs. There were however correlations between morphosyntactic accuracy and selective auditory attention which, in line with previous work, suggests a specific link between morphosyntax and the ability to suppress irrelevant stimuli. In Sweden, socioeconomic differences are rather small and preschool is more or less universal, but nevertheless, aspects of parental SES predicted children’s performance on all measures, and bi-/multilingual children performed lower on language also when controlling for SES, highlighting the need for interventions to reduce inequalities in educational outcomes already in preschool. A female advantage was found for both language and EFs, whereas preschool attendance and quality were not significantly related to outcome measures. Future work should include longitudinal studies of language and EF development, include children from diverse SES backgrounds and contribute toward a theoretical framework that further clarifies the language-EF relationship.